Adaptation of the Quality Indicator for Rehabilitative Care (QuIRC) for use in mental health supported accommodation services (QuIRC-SA). Issue 1 (December 2016) - Killaspy, Helen; White, Sarah; Dowling, Sarah; Krotofil, Joanna; McPherson, Peter; Sandhu, Sima; Arbuthnott, Maurice; Curtis, Sarah; Leavey, Gerard; Priebe, Stefan; Shepherd, Geoff; King, Michael
Abstract Background No standardised tools for assessing the quality of specialist mental health supported accommodation services exist. To address this, we adapted the Quality Indicator for Rehabilitative care-QuIRC-that was originally developed to assess the quality of longer term inpatient and community based mental health facilities. The QuIRC, which is completed by the service manager and gives ratings of seven domains of care, has good psychometric properties. Methods Focus groups with staff of the three main types of supported accommodation in the UK (residential care, supported housing and floating outreach services) were carried out to identify potential amendments to the QuIRC. Additional advice was gained from consultation with three expert panels, two of which comprised service users with lived experience of mental health and supported accommodation services. The amended QuIRC (QuIRC-SA) was piloted with a manager of each of the three service types. Item response variance, inter-rater reliability and internal consistency were assessed in a random sample of 52 services. Factorial structure and discriminant validity were assessed in a larger random sample of 87 services. Results The QuIRC-SA comprised 143 items of which only 18 items showed a narrow range of response and five items had poor inter-rater reliability. The tool showed good discriminant validity, with supported housing services generally scoring higher than the other two types of supported accommodation on most domains. Exploratory factor analysis showed that the QuIRC-SA items loaded onto the domains to which they had been allocated. Conclusions The QuIRC-SA is the first standardised tool for quality assessment of specialist mental health supported accommodation services. Its psychometric properties mean that it has potential for use in research as well as audit and quality improvement programmes. A web based application is being developed to make it more accessible which will produce a printable report for the service manager about the performance of their service, comparison data for similar services and suggestions on how to improve service quality.